The Changes of Students’ Toefl Score After One Year Learning - Ienneke Indra Dewi; Darna Darna; Djuria Suprato (Humaniora, 2015)
BINUS students are supposed to increase their English competence indicated by their TOEFL scores. This paper aims to observe the differences between studens TOEFL scores obtained when they entered BINUS and the scores after they joined TOEFL courses at BINUS for one year. The participants were 121 students. The data for the entrance test were taken from the BINUS data center and the final test data were taken from their final test at English class. The data were analysed using statistics especially the descriptive statistics, comparing means, and correlation. To support the quantative data, a set of questionnaires was distributed to those 121 students. The results show that the students’ TOEFL scores have increased significantly in the final test compared to those in the entrance test. The low achiever students showed a better performance than the higher ones. Students’ motivation and background support their English study. Students proved to have the most problem in listening. The results of the research are expected to be the input for English lecturers to improve their teaching especially the existence of SALLC (Self Access Language Learning Center).